Implementation and Challanges of Vocational Education for Students Special Needs - Ardiani, Rahma; Yoenanto, Nono Hery (JPI (Jurnal Pendidikan Inklusi), 2024)
The implementation of vocational classes is necessary so that student with special needs can prepare for the job competition. Trough vocational classes, student can improve their skill which support a field of work. The success of vocational classes requires family social support, teachers, experts, schools, and external participants. The aim of this research is to describe the implementation of vocational classes that have been applied to student who has special needs. The research method is narrative literature review. The results explain vocational class program which packaged into a career guidance, which contains pre-vocational, vocational, and postvocational. Types of vocational classes include culinary, salon, horticulture, sewing, nail art gradation, barbering, making ceramics, garden lighting, water mills, laundry, cleaning service, hydroponics, drawing, and colouring. Obstacles that arise are low student motivation, limited school funding, and inadequate tools. The solution can be proposed is career guidance in vocatonal education. Family social support and financial capabilities are needed for the success of vocational education. Keywords: Students with Special Needs, Vocational Education